Two-step evolution of HIV-1 budding system leading to pandemic in the human population - Yoriyuki Konno; Keiya Uriu; Takayuki Chikata; Toru Takada; Jun-ichi Kurita; Mahoko Takahashi Ueda; Saiful Islam; Benjy Jek Yang Tan; Jumpei Ito; Hirofumi Aso; Ryuichi Kumata; Carolyn Williamson; et al. (Cell Reports, 2024)
Summary: The pandemic HIV-1, HIV-1 group M, emerged from a single spillover event of its ancestral lentivirus from a chimpanzee. During human-to-human spread worldwide, HIV-1 diversified into multiple subtypes. Here, our interdisciplinary investigation mainly sheds light on the evolutionary scenario of the viral budding system of HIV-1 subtype C (HIV-1C), a most successfully spread subtype. Of the two amino acid motifs for HIV-1 budding, the P(T/S)AP and YPxL motifs, HIV-1C loses the YPxL motif. Our data imply that HIV-1C might lose this motif to evade immune pressure. Additionally, the P(T/S)AP motif is duplicated dependently of the level of HIV-1 spread in the human population, and >20% of HIV-1C harbored the duplicated P(T/S)AP motif. We further show that the duplication of the P(T/S)AP motif is caused by the expansion of the CTG triplet repeat. Altogether, our results suggest that HIV-1 has experienced a two-step evolution of the viral budding process during human-to-human spread worldwide.